1998
DOI: 10.1111/j.1399-0039.1998.tb02273.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CD44 exon v10 in B‐cell activation

Abstract: The family of CD44 glycoproteins has been suggested to be involved in lymphocyte homing, maturation and activation. Using in vitro blocking studies with a monoclonal antibody, we here addressed the question of functional activity of CD44 variant exon v10 (CD44v10) in B-cell activation. We became interested in this question by the observation that CD44v10O was transiently expressed on activated T cells, B cells and monocytes as well as on a subpopulation of bone marrow cells. A potential ligand, as revealed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Furthermore, transplanted HSC maturation towards T and B cells was more severely impaired in EL4 than EL4-v10 TB and was strongly affected by IM7. Instead, K926 only affected B cell maturation, which is in line with our earlier report on CD44v10 expression in B progenitor cells [30]. In vitro cocultures confirmed that EL4 more efficiently than EL4-v10 competed with HSC for BM-Str adhesion.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, transplanted HSC maturation towards T and B cells was more severely impaired in EL4 than EL4-v10 TB and was strongly affected by IM7. Instead, K926 only affected B cell maturation, which is in line with our earlier report on CD44v10 expression in B progenitor cells [30]. In vitro cocultures confirmed that EL4 more efficiently than EL4-v10 competed with HSC for BM-Str adhesion.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, fewer HSC were recovered from late EL4 than EL4-v10 TB (Figure 2C). In late EL4-v10 TB a minor retention of Gr1 + cells in the BM and a slight reduction in serum IgG was noted (Figure 2C and D), which is in line with CD44v10 being engaged in monocyte and B cell maturation [30]. Reduced recovery of HSC in IM7-treated late TB could be in line with IM7, distinct to K926, interfering with HSC embedding in the osteogenic niche.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Interestingly, the costimulatory effect was only observed with IM-7, but not with the anti-CD44 antibody KM81, which occupies the hyaluronic acid binding site of CD44. Cross-linking of CD44v10, which is weakly expressed on SC [27], was ineffective ( Fig. 2A).…”
Section: Inhibition Of Il-2 Secretion By a Cd44 Receptor Globulin Andmentioning
confidence: 99%
“…Side effects should be minimized, as CD44v expression is far more restricted, with few exceptions, and interacts only weakly in non‐transformed cells. It is also weakly expressed on subpopulations of macrophages (Mφ), activated Th1 cells and B progenitor cells 34 , 35 , 36 , 37 but more highly expressed on keratinocytes 38 . In some organ‐specific autoimmune diseases, CD44v10 is expressed in memory T helper (Th) and dendritic cells and contributes to progression by recruiting Th and supporting Th longevity, 34 which can be blocked by anti‐CD44v10 39 , 40 , 41 .…”
mentioning
confidence: 99%